Two new species of Selitrichodes (Hymenoptera: Eulophidae: Tetrastichinae) inducing galls on Casuarina (Casuarinaceae) - Fisher, Nicole; Moore, Aubrey; Brown, Bradley; Purcell, Matthew; Taylor, Gary S.; Salle, John La (Zootaxa, 2014)
Two new species of gall-inducing wasps, Selitrichodes casuarinae Fisher & La Salle sp. n. and Selitrichodes utilis Fisher & La Salle sp. n., are described from Micronesia (Guam, Rota and Palau Islands) and Australia respectively. These species induce galls on Casuarina and can cause extensive damage to the trees. Their status as pest or beneficial species is discussed.